Clinical and laboratory profile of children admitted with measles in a tertiary care teaching hospital - P, Leela Kumari; T, Ranjith Kumar (Indian Journal of Child Health, 2018)
Background: Measles is a vaccine-preventable viral illness associated with substantial childhood morbidity and mortality. Recently, changing trends in the occurrence of measles are noted like incidence in younger infants and in those who have received measles vaccine. Objectives: The objective was to study the clinical profile of children with measles and to study the usefulness of polymerase chain reaction (PCR) in diagnosing measles and to study the measles-specific immunoglobulin M (IgM) response in children with measles. Materials and Methods: This study was done in the Pediatrics Department of a Tertiary Care Center, and the study population was children up to 12 years of age admitted in the setting with a clinical diagnosis of measles during the study period and who were laboratory confirmed by PCR/IgM ELISA or both. Results: Of 173 clinically diagnosed cases, 149 laboratory confirmed cases were taken for analysis and studied. Of these, 47% of cases were below 9 months. Newborns constituted 2.01% of the total cases. The mean age was 13 months and the male:female ratio was 1.13:1. A total of 24.8% children were unimmunized, 16.77% had a single dose, and 8.72% had 2 doses of measles vaccine. Overall mortality was 0.67% and bronchopneumonia was the major complication (76.5%). Among immunized children with measles confirmed by PCR, measles-specific IgM response was reactive in 36.4% of cases. In the early phase of measles (within 3 days) confirmed by PCR, IgM response was inconclusive in 60% of cases. Conclusion: In our study, 47% of the cases of measles were below 9 months; therefore, the age of measles vaccination may be reconsidered. Among eligible cases (>9 months), 24.83% were not immunized for measles which indicates that measles immunization coverage should be increased. Among the measles cases, 25% had measles vaccination which highlights the need to check for the determinants of vaccine failure. In our study, the RT-PCR was found to be useful for early diagnosis of measles and for diagnosis in immunized children.